Evaluasi Modular UX terhadap Fitur Narasi Budaya pada Sistem Rekomendasi Makanan - Utomo, Prayudi; Annisa; Djatna, Taufik; Ardiansyah, Firman; Utomo, Prayudi Utomo (Sekolah Sains Data, Matematika, dan Informatika. Institut Pertanian Bogor, 2025)
This study designs and evaluates a cultural narrative feature in a food recommender system to enhance emotional engagement and cultural relevance while preserving usability. The feature uses progressive disclosure and is implemented as a modular interface component that embeds local food stories within recommendation cards. Fifteen users participated in a task-based, triangulated UX evaluation (usability testing, heuristic evaluation, and thematic analysis). Although only 25% of participants interacted with the narrative element, those who did spent more than twice as long engaging with the content. Heuristic findings indicated issues in system-status visibility and visual transition, while thematic insights showed curiosity, emotional recall, and cultural identification. The results suggest that optional, contextual narratives can enrich recommender-system UX and can be integrated as maintainable modular components for iterative refinement